2021
DOI: 10.1155/2021/7404671
|View full text |Cite|
|
Sign up to set email alerts
|

Mir-204 Regulates LPS-Induced A549 Cell Damage by Targeting FOXK2

Abstract: Objective. To assess whether miR-204 and HA affect A549 cell injury induced by lipopolysaccharide. Material and Methods. A549 cells were treated with hirsutanol A, and cell damage was induced by LPS followed by analysis of cell proliferation by CCK-8, cell apoptosis by flow cytometry, apoptosis-related protein expression by western blot, downstream target of miR-20 by dual-luciferase reporter gene, and inflammatory factors by ELISA and PCR. Results. LPS can significantly inhibit the viability of A549 cells, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The results become more diverse at later time points (day six vs. day three). We observed that the three MHC-IImacrophage and monocyte subtypes partially overlap in Foxk2, Rora, and Ing4 genes that are associated with cytokine production in response to LPS [55,56], while for the MHC-II + subtype, we predicted autophagy-related genes Rb1cc1, Rb1, and Hdac2 [57][58][59]. Whether or not this difference is caused by MHC-II is yet to be determined, as only limited evidence connects MHC-II with the predicted genes.…”
Section: Immune Cell Activation Modulates Gene Regulatory Network Of ...mentioning
confidence: 86%
“…The results become more diverse at later time points (day six vs. day three). We observed that the three MHC-IImacrophage and monocyte subtypes partially overlap in Foxk2, Rora, and Ing4 genes that are associated with cytokine production in response to LPS [55,56], while for the MHC-II + subtype, we predicted autophagy-related genes Rb1cc1, Rb1, and Hdac2 [57][58][59]. Whether or not this difference is caused by MHC-II is yet to be determined, as only limited evidence connects MHC-II with the predicted genes.…”
Section: Immune Cell Activation Modulates Gene Regulatory Network Of ...mentioning
confidence: 86%
“…The low level of miR-140-3p lost the inhibitory effect on the expression of FOXK2, thereby enhancing the angiogenic function of ECs (135). In hirsutanol A (HA)-pretreated A549 cells, upregulation of miR-204 directly targets FOXK2, promoting cell viability by reducing apoptosis and inhibiting the release of inflammatory factors by attenuating NF-κB activation (136).…”
Section: Foxk2 and Sumoylation And Ubiquitinationmentioning
confidence: 99%
“…FOXK2 promotes colorectal cancer proliferation and metastasis by increasing the expression of Zinc finger E-box binding homeobox 1 and EGFR (198). Studies have shown that miR-204 is a novel regulator of the innate immune response (246) that targets FOXK2 by inhibiting the NF-κB pathway, thereby reducing apoptosis and increasing cell viability (136,247,248). The NF-κB pathway has been shown to be activated in colon cancer, controlling the expression of multiple target genes, promoting cell proliferation and linking immunomodulatory, inflammatory and carcinogenic responses (249).…”
Section: Foxk2 and Virusesmentioning
confidence: 99%
“…Cell systems do not entirely replicate the physiological complexity of innate immune recognition, but they provide a reliable and effective model for controlled studies, including the ability to expose cells to individual pathogens or molecules and measure responses over time. However, most cell studies are limited in scope by focusing on a few key cytokine and chemokine targets and avoiding biological variation by using a small number of replicates [ 13 , 14 ]. Typically, these studies are designed to measure either transcription (mRNA) or protein responses, not both, resulting in limited data sets allowing for a direct comparison of potential mRNA and protein biomarkers of host responses to specific stimuli [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%